Historical spatial structures in small towns and their role in the cultural landscape: a case study of towns in the polish region of Warmia - Zagroba, Marek (Bulletin of Geography. Socio-economic Series, 2024)
Historical town centers have a different layout and functions than do contemporary urban districts. The urban layout and architecture of medieval towns constitute tangible cultural heritage that shapes the local landscape. The aim of this study was to analyze and evaluate historical spatial structures in small towns, and to describe their role in the evolution of the regional cultural landscape. The study examined medieval towns in the region of Warmia in north-eastern Poland. An attempt was also made to explore the impact that historical towns exert on the local cultural landscape. The study demonstrated that a medieval urban spatial layout makes a fundamental contribution to the local landscape and regional identity. The study also revealed that well-preserved historical structures can drive local development and effectively promote regions.